Politik Islam di Indonesia: Ideologi Partai Masyumi Masa Orde Lama dan Partai Kebangkitan Bangsa (PKB) Masa Reformasi - Trei Ilham Supawi (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
This article discusses Islamic politics in Indonesia through the Masyumi Party during the Old Order and the Partai Kebangkitan Bangsa (PKB) during the Reformation Era. Writing this article using descriptive analysis and historical research methods. The historical method is divided into four steps, namely: heuristics, criticism, interpretation, and historiography. The results showed that Masyumi was an Islamic party which became a unifying pillar of the nation during the Old Order. Masyumi's struggle in upholding Islamic law as the state ideology did not run smoothly after the changes that occurred in the seven words and the Jakarta Charter. Unlike the case with the Partai Kebangkitan Bangsa (PKB), which was founded during the Reformation period by the Nahdlatul Ulama (NU) mass organization. PKB aims to convey the aspirations of the people, especially NU members who want freedom in expressing opinions on issues in the government. PKB has a political basis based on Pancasila, not Islam. Despite carrying different goals, these two parties continue to run the parliamentary line because of the struggle for Islamic politics in Indonesia.